EFEKTIVITAS SCIENTIFIC APPROACH WITH GUIDED EXPERIMENT PADA PEMBELAJARAN IPA UNTUK MEMBERDAYAKAN KETERAMPILAN PROSES SAINS SISWA SEKOLAH DASAR - Prasasti, Pinkan Amita Tri (Universitas Muhammadiyah Surakarta, 2017)
The purpose of this study was to determine the effectiveness of Scientific Approach with Guided Experiment on learning science to empower Science Process Skills. This study is a quasi-experimental research. The study design used Posttest Only Control Group Design is divided into two groups: an experimental group using a Scientific Approach with Guided Experiment and control groups using the method of lecture and discussion. The population in the study were all students of class V SD SD N Banjarejo Academic Year 2016/2017 by the number of 122 students. The sampling technique is cluster random sampling done by taking a sample of 37 fifth grade students in the experimental class A and 36 students of class V C in the control class. The instrument used was a questionnaire, observation sheets, interview and test. Data science process skills were tested by t-test. The results of the analysis of hypothesis testing using t-test with significance level of 5% yield significance at p = 0.000 and the value = 0.018. Classes that implement Scieintific aproach with Guided Experiment has an average KPS higher than the class without using Scieintific aproach with Guided Experiment in the amount of 82.34 and 71.14. Based on the results of hypothesis testing can dismpulkan that Scieintific aproach with Guided Experiment in empowering capabilities of Science Process Skills Student GradeV SD N Banjarejo Madiun Academic Year 2016/2017.